Kontribusi Industri Nasional Terhadap Pembangunan Di Indonesia - Muhammad Ilham Januarta; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research falls into the qualitative descriptive category using primary and secondary data in order to analyze the development of manufacturing industry in Indonesia which tends to deindustrialization, whereas the manufacturing industry has a big contribution to the Gross Domestic Product, the absorption of employment, the income tax and the foreign exchange, the creation Value added, and technology transfer. The results of the research show that in order to create a tough industry in 2035, a strong foundation is required, and an inclusive transformation of Indonesia's economy in the manufacturing industry through the use of added value natural resources, the readiness of human resources and the supply of energy from renewable sources. The industry structure that Indonesia needs is an industry that has strong and synergistic links between industrial sub-sectors and with various other economic sectors, has high local content, can grow sustainably, and has resistance to the world economic turmoil.